2007
DOI: 10.1073/pnas.0607956104
|View full text |Cite
|
Sign up to set email alerts
|

Impaired FGF signaling contributes to cleft lip and palate

Abstract: Nonsyndromic cleft lip and palate (NS CLP) is a complex birth defect resulting from a combination of genetic and environmental factors. Several members of the FGF and FGFR families are expressed during craniofacial development and can rarely harbor mutations that result in human clefting syndromes. We hypothesized that disruptions in this pathway might also contribute to NS CLP. We sequenced the coding regions and performed association testing on 12 genes (FGFR1, FGFR2, FGFR3, FGF2, FGF3, FGF4, FGF7, FGF8, FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
242
1
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 257 publications
(266 citation statements)
references
References 57 publications
7
242
1
16
Order By: Relevance
“…Our results partially corroborate the association data presented by Riley et al [2007] in which several genes (FGF3, FGF7, FGF10, FGF18, and FGFR1) demonstrated a trend for association with nonsyndromic cleft lip and palate. In addition, the diversity in the binding specificity of FGF receptors for FGFs clearly can lead to a large combinatorial set of possible interactions.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Our results partially corroborate the association data presented by Riley et al [2007] in which several genes (FGF3, FGF7, FGF10, FGF18, and FGFR1) demonstrated a trend for association with nonsyndromic cleft lip and palate. In addition, the diversity in the binding specificity of FGF receptors for FGFs clearly can lead to a large combinatorial set of possible interactions.…”
supporting
confidence: 91%
“…Mutations in FGFR1 cause autosomal dominant Kallmann syndrome, which includes clefts in 30% of the cases and tooth agenesis in 7% [Dodé et al, 2003]. Sequencing of the coding region of genes in the FGF signaling pathway in nonsyndromic cleft cases revealed that missense and nonsense mutations in FGF genes might contribute to approximately 3% of nonsyndromic cleft lip and palate [Riley et al, 2007].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Hh signaling is crucial for palatogenesis in humans and zebrafish 3,4,7 . Zebrafish and amniotes also share expression patterns of palatogenic genes such as Shh 4,8 , Fgf8 4,9,10 and Pdgf receptor alpha (Pdgfra) [11][12][13] .In mouse, the Pdgf family consists of four soluble ligands, Pdgfa, Pdgfb, Pdgfc, and Pdgfd as well as two receptor tyrosine kinases, Pdgfra and Pdgfrb 14 . Pdgf signaling regulates a myriad of biological processes as demonstrated by analyses of mouse Pdgf ligand and receptor mutants 14 .…”
mentioning
confidence: 99%